Notch3-Dependent Effects on Adult Neurogenesis and Hippocampus-Dependent Learning in a Modified Transgenic Model of CADASIL - Ehret, Fanny; Moreno Traspas, Ricardo; Neumuth, Marie-Theres; Hamann, Bianca; Lasse, Daniela; Kempermann, Gerd (Frontiers in Aging Neuroscience, 2021)
We and others have reported that Notch3 is a regulator of adult hippocampal neurogenesis. Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL), the most common genetic form of vascular dementia, is caused by mutations in Notch3. The present study intended to investigate whether there is a correlation between altered adult hippocampal neurogenesis and spatial memory performance in CADASIL transgenic mice. To overcome visual disabilities that hampered behavioural testing of the original mice (on an FVB background) we back-crossed the existing TgN3R169C CADASIL mouse model onto the C57BL/6J background. These animals showed an age-dependent increase in the pathognomonic granular osmiophilic material (GOM) deposition in the hippocampus. Analysis in the Morris water maze task at an age of 6 and 12 months revealed deficits in re-learning and perseverance in the CADASIL transgenic mice. Overexpression of Notch3 alone resulted in deficits in the use of spatial strategies and diminished adult neurogenesis in both age groups. The additional CADASIL mutation compensated the effect on strategy usage but not on adult neurogenesis. In brain bank tissue samples from deceased CADASIL patients we found signs of new neurons, as assessed by calretinin immunohistochemistry, but no conclusive quantification was possible. In summary, while our study confirmed the role of Notch3 in adult neurogenesis, we found a specific effect of the CADASIL mutation only on the reversion of the Notch3 effect on behaviour, particularly visible at 6 months of age, consistent with a loss of function. The mutation did not revert the Notch3-dependent changes in adult neurogenesis or otherwise affected adult neurogenesis in this model.